Kajian Yuridis Hak Imunitas Anggota DPR RI dalam Prinsip Equality Before the Law Menurut Undang-Undang Nomor 2 Tahun 2018 Perubahan-Perubahan Ke Dua Atas Undang-Undang Nomor 17 Tahun 2014 Tentang MPR, DPR, DPD dan DPRD - Ainuddin, Emha; Purwanto, Djoko (Journal of Contemporary Law Studies, 2023)
This research was carried out with the aim of finding out and studying more deeply the Immunity Rights in the principle of Equality Before the Law held by members of the DPR RI. The research method used is normative juridical. The results of the research show that: The immunity rights of members of the DPR are interpreted as the right of members of the people's representative institutions to discuss or state in writing all matters within the institution without being sued before a court. With the right to immunity, members of the DPR are not immune from the law, because the right to immunity does not apply in general, apart from that, Indonesia also upholds the principle of equality before the law. The articles that regulate the DPR's immunity rights, such as Articles 224 and 245, were submitted for review to the Constitutional Court and then decided with decision Number 76/PUU- regarding granting permission to examine members of the DPR who are summoned in the context of suspected criminal acts, the authority of which was originally held by the MKD in article 245 has been removed by the MK.